The Heparan Sulfate Binding Peptide in Tumor Progression of Triple-Negative Breast Cancer - Melo, Carina Mucciolo; Wang, Huawei; Fujimura, Ken; Strnadel, Jan; Meneghetti, Maria Cecília Zorél; Nader, Helena Bonciani; Klemke, Richard L.; Pinhal, Maria Aparecida Silva (Frontiers in Oncology, 2021)
Angiogenesis is the formation of new vessels from pre-existing vasculature. The heparan sulfate chains from endothelial cell proteoglycans interact with the major angiogenic factors, regulating blood vessels´ formation. Since the FDA´s first approval, anti-angiogenic therapy has shown tumor progression inhibition and increased patient survival. Previous work in our group has selected an HS-binding peptide using a phage display system. Therefore, we investigated the effect of the selected peptide in angiogenesis and tumor progression. The HS-binding peptide showed a higher affinity for heparin N-sulfated and 2-O-sulfated. The HS-binding peptide was able to inhibit the proliferation of human endothelial umbilical cord cells. The analysis demonstrated that the HS-binding peptide inhibited proliferation modulating FGF-2. There was a significant alteration in the tube formation when human endothelial cells were treated with HS-binding peptide. Therefore, we investigate whether there is some effect of the HS-binding peptide in vivo. HS-binding peptide inhibits the formation of sub-intestinal blood vessels of zebrafish embryos. The data ex vivo using mice aorta corroborate the in vitro and in vivo experiments. Patient-derived xenotransplant cells were injected in zebrafish embryos and subsequently treated with HS-binding peptide, the tumor size decreased.